Re/Un/Discover: An embodied heuristic for uncertainties in social work practice - Keenan, Elizabeth King (Australian Social Work, 2021)
Social workers have always worked with and within uncertainties in practice, but the COVID-19 pandemic is amplifying the frequency and degree of uncertainty across ecological levels. Social workers need enhanced capacity to work with these uncertainties and the impact on individual and collective wellbeing. The RE/UN/DIScover heuristic guides social workers’ responses to the wide range of practice uncertainties experienced in the moment and over time. Drawing on understandings of embodied wellbeing from interpersonal neurobiology and the power relations manifest in intersectional positionality, RE/UN/DIScover offers embodied, iterative practices to access the wealth of capabilities within self and others. IMPLICATIONS Disruptions and uncertainties connected with pandemics, economic recessions, continued systemic injustices and other human-made problems can challenge social workers and impact the wellbeing of individuals and communities. Heuristics are guides that sort, order, and inform decisions and actions. The RE/UN/DIScover heuristic uses knowledge about embodied wellbeing and various forms of power to guide social workers. RE/UN/DIScover offers social workers practices to use with uncertainties both in the moment and over time. © 2020 Australian Association of Social Workers.
3 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85097057855
Keywords: dept.swk; peer-reviewed